Theoretical and experimental research to develop of a new wind turbine construction with directing device Annotation (Journal of Mathematics Mechanics and Computer Science, 2015)
This article presents the results of theoretical and experimental studies on the development of a new design of the wind-powered assembly with a guiding vane. The object of the theoretical andexperimental research is to improve the efficiency of wind turbines. One of the urgent problems is development of new useful windmill (wind turbine) to provide electricity to remotely locatedvillages, with limited accesses to electrical power. To address this issue, new models of vortex wind generators, with guiding vanes, were presented. Also, drawings and models of vortex windgenerators were developed, and laboratory experiments were conducted on different models As a result, of the research, the most optimal model has been chosen and was fully investigated.Aerodynamic parameters of the vortex wind generator were studied. The corresponding number of revolutions of rotor blades in wind flow were acquired. In the study, the need for verticalarrangement for upper cylindrical pipe was identified.. Moreover, it was observed that directing wind into multiple guiding channels, increases the rpm. Model of the assembly was built and numerically studied in the COMSOL Myltiphysics software. The same program was used to built geometric model. Change of velocity and pressure acting on the guide wall when wind flow around a constructed model were determined as well. Curved andrectilinear forms of the guiding walls were considered, and results of research in these two cases were compared.
Keywords: wind power turbine; whirling wind power turbine; energy potential; guide vanes; the program COMSOL Multiphysics; wind generator